Evaluation method of quran memorization at muhammadiyah 5 junior high school surakarta - Akbar Tanjung; Haris Ibadurrahman; Abdunrorma Sama Alee (Yayasan Azhar Amanaa Yogyakarta, 2024)
Becoming a Hafidz or having a generation that memorizes the Qur'an is the hope of Muslims, especially at SMP Muhammadiyah 5 Surakarta because this is a glory that can bring its owner happiness in this world and the hereafter and can even be an achievement and pride in itself for the individual. Muhammadiyah Middle School 5 Surakarta. However, the current reality is that many institutions or agencies that organize Tahfidzul Qur'an have not yet shown significant results in bringing back generations of Qur'an memorizers. This problem cannot be separated from the learning methods used. This research uses qualitative methods, the data sources used are teachers and students at SMP Muhammadiyah 5 Surakarta, data collection techniques are observation, interviews and documentation. The findings of this research show that the use of inconsistent methods in memorizing the Qur'an produces the following results: 1). Students experience difficulty in maintaining their memorization, 2) Students feel bored and have difficulty memorizing, 3) Educators will find it difficult to provide value for students' learning outcomes. From these findings it can be concluded that inconsistent methods for memorizing the Qur'an cannot be fully applied in learning because the results are not relevant for us to implement, so there must be an evaluation and development of Al-Qur'an learning methods.